Heightened activity in social reward networks is associated with adolescents' risky sexual behaviors. (October 2017) - Eckstrand, Kristen L.; Choukas-Bradley, Sophia; Mohanty, Arpita; Cross, Marissa; Allen, Nicholas B.; Silk, Jennifer S.; Jones, Neil P.; Forbes, Erika E.
Abstract: Adolescent sexual risk behavior can lead to serious health consequences, yet few investigations have addressed its neurodevelopmental mechanisms. Social neurocircuitry is postulated to underlie the development of risky sexual behavior, and response to social reward may be especially relevant. Typically developing adolescents ( N  = 47; 18M, 29F; 16.3 ± 1.4 years; 42.5% sexual intercourse experience) completed a social reward fMRI task and reported their sexual risk behaviors (e.g., lifetime sexual partners) on the Youth Risk Behavior Survey (YRBS). Neural response and functional connectivity to social reward were compared for adolescents with higher- and lower-risk sexual behavior. Adolescents with higher-risk sexual behaviors demonstrated increased activation in the right precuneus and the right temporoparietal junction during receipt of social reward. Adolescents with higher-risk sexual behaviors also demonstrated greater functional connectivity between the precuneus and the temporoparietal junction bilaterally, dorsal medial prefrontal cortex, and left anterior insula/ventrolateral prefrontal cortex. The greater activation and functional connectivity in self-referential, social reward, and affective processing regions among higher sexual risk adolescents underscores the importance of social influence underlying sexual risk behaviors. Furthermore, results suggest an orientation towards and sensitivity to social rewards among youth engaging in higher-risk sexual behavior, perhaps as a consequence of or vulnerability to such behavior.